2014
DOI: 10.1158/1535-7163.mct-13-1091
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monocarboxylate Transporter-1 (MCT1) by AZD3965 Enhances Radiosensitivity by Reducing Lactate Transport

Abstract: Inhibition of the monocarboxylate transporter MCT1 by AZD3965 results in an increase in glycolysis in human tumor cell lines and xenografts. This is indicated by changes in the levels of specific glycolytic metabolites and in changes in glycolytic enzyme kinetics. These drug-induced metabolic changes translate into an inhibition of tumor growth in vivo. Thus, we combined AZD3965 with fractionated radiation to treat small cell lung cancer (SCLC) xenografts and showed that the combination provided a significantl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 48 publications
3
139
0
Order By: Relevance
“…In an effort to alter lactate transport, small molecule inhibitors have been designed against both MCT1 and MCT4 [91] [92]. Drugs that inhibit mitochondrial OXPHOS are in early phase clinical trials in diseases such as AML, prostate cancer, and colorectal cancer [93] [94] [95].…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to alter lactate transport, small molecule inhibitors have been designed against both MCT1 and MCT4 [91] [92]. Drugs that inhibit mitochondrial OXPHOS are in early phase clinical trials in diseases such as AML, prostate cancer, and colorectal cancer [93] [94] [95].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MCTs have been shown to impact the effects of chemotherapeutic agents such as 3-bromopyruvate and dichloroacetate by modulating their delivery to the cell [71-73]. The MCTs can also sensitize cells to radiation therapy [74, 75]. As a result, MCTs have been considered a therapeutic target, either alone or in combination with other therapies [61, 69, 70, 74, 76-79].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided proof that targeting these MCTs can cause an initial build-up of lactate and an altered intracellular pH, followed by collapse of the glycolytic metabolic flux, and can facilitate glioma cell death. Separate studies by us and others have also shown that inhibition of glycolysis by interfering with lactate efflux can enhance radiosensitivity of these frequently radioresistant tumors by up to 10-fold [11], [24].…”
Section: Introductionmentioning
confidence: 92%